Comparing Associations Between the Built Environment and Walking in Rural Small Towns and a Large Metropolitan Area. (January 2016) - Stewart, Orion T.; Vernez Moudon, Anne; Saelens, Brian E.; Lee, Chanam; Kang, Bumjoon; Doescher, Mark P.
The association between the built environment (BE) and walking has been studied extensively in urban areas, yet little is known whether the same associations hold for smaller, rural towns. This analysis examined objective measures of the BE around participants' residence and their utilitarian and recreational walking from two studies, one in the urban Seattle area ( n = 464) and the other in nine small U.S. towns ( n = 299). After adjusting for sociodemographics, small town residents walked less for utilitarian purposes but more for recreational purposes. These differences were largely explained by differential associations of the BE on walking in the two settings. In Seattle, the number of neighborhood restaurants was positively associated with utilitarian walking, but in small towns, the association was negative. In small towns, perception of slow traffic on nearby streets was positively associated with recreational walking, but not in Seattle. These observations suggest that urban–rural context matters when planning BE interventions to support walking.